ANALISIS KEPUASAN SISWA TERHADAP QUALITY OF SERVICE JARINGAN WLAN SMKN 2 PADANG MENGGUNAKAN METODE FUZZY-SERVQUAL - Agung Rorhi Prayudha; Elfi Tasrif; Nurindah Dwiyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
Satisfaction is the level of one's feelings after comparing the performance (outcome) that he felt compared to his expectations. Servqual method combined with fuzzy logic with the aim that the measurement of perceptions and expectations of students can be measured more precisely with more objective data.The purpose of this research is to measure the level of student satisfaction on Quality of Service WLAN network SMKN 2 Padang using Fuzzy-Servqual method. The method used in determining the level of student satisfaction is Servqual method that contains five dimensions of reliability, responsiveness, tangibles, security and access. The results of the analysis show that the overall gap is negative, which means that students are not satisfied with WLAN SMKN 2 Padang service. The gap value of each dimension in the Accounting department is reliability = -0.580; responsiveness = -0.4461; tangible = -0.603; security = -0.146; access = -0.4463. While in the tourism business travel department (UPW) gap value for the dimensions of reliability = -1,620; responsiveness = -1,460; tangible = -1,897; security = -1,517; access = -1,260. For the overall gap Accounting majors = -0.451, while the tourism business travel (UPW) = -1.540. Keywords: Fuzzy-Servqual, gap, WLAN